2021
DOI: 10.1371/journal.pone.0247646
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and microbiological characterization of sepsis and evaluation of sepsis scores

Abstract: Background Despite the necessity of early recognition for an optimal outcome, sepsis often remains unrecognized. Available tools for early recognition are rarely evaluated in low- and middle-income countries. In this study, we analyzed the spectrum, treatment and outcome of sepsis at an Ethiopian tertiary hospital and evaluated recommended sepsis scores. Methods Patients with an infection and ≥2 SIRS criteria were screened for sepsis by SOFA scoring. From septic patients, socioeconomic and clinical data as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 44 publications
5
8
1
Order By: Relevance
“…Although this result is in line with other studies 13 , some scepticism was also observed 14 , 15 . As a result, the real advantages of sepsis bundles have been questioned, and uncertain data are currently available.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Although this result is in line with other studies 13 , some scepticism was also observed 14 , 15 . As a result, the real advantages of sepsis bundles have been questioned, and uncertain data are currently available.…”
Section: Discussionsupporting
confidence: 93%
“…The main feature of our study has been the inclusion of those patients with positive BC, rather than all those with a clinical suspicion of sepsis, as the sepsis clinical presentation might frequently resemble that of other morbid conditions 16 . Although we agree with Fuchs et al’s findings that a standardised method of BCs may positively contribute to optimised management of sepsis, and consequently to an improved survival rate of septic patients 14 , it should be mentioned that BCs collection procedures have been already standardised during period A in our ER. This virtuous practice, which had already been introduced in the period A, and consistently maintained throughout the period B, allowed to attain a positive BCs rate around 30%.…”
Section: Discussionsupporting
confidence: 90%
“…Although this result is in line with other studies[16], some skepticism was also observed [17,18]. As a result, the real advantages of sepsis bundles have been questioned, and uncertain data are currently available.…”
Section: Discussionsupporting
confidence: 89%
“…Hence, the septic clinical presentation might frequently resemble that of other morbid conidtions [19]. Firstly, although we agree with Fuchs et al's ndings that a standardized method of BCs may positively contribute to optimized management of sepsis, and consequently to an improved survival rate of septic patients [17], it should be mentioned that BCs collection procedures have been already standardized during period A in our ER. This virtuous practice, which had already been introduced in the period A, and consistently maintained throughout the period B, allowed to attain a positive BCs rate around 30%.…”
Section: Discussionsupporting
confidence: 70%
“…Continued extensive empiric use of 3GC in the absence of AST might lead to a further decrease in antimicrobial activity and therefore increase the burden on resource-limited health care systems of the countries affected (8). This development can also be observed locally and previous investigations at the study site show that the effectiveness of the limited choice of available antimicrobials is diminished due to the high rate of ESBL-producing GNB (9). There is an increasing need for strategies to enhance prudent use of antibiotics in the country due to the alarming spread of ESBL-producing GNB leading to high rates of infections due to MDR, which are di cult if not impossible to treat (10,11).…”
Section: Introductionsupporting
confidence: 54%